Profitabilitas (ROA) Dipengaruhi Oleh Manajemen Kas - Apriyanto, Riko; Surachim, Ahim (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2017)
The Purpose of this research isÂ  to find out the description of Profitability (ROA) that is influenced by cash management. This type of research used are descriptive, verifikatif. The sampling technique used documentation study. Data analysis technique used is simple linear regresion with computer software SPSS 21.0.Â  Based on the results of the research that cash management influence on profitability. The differences in this study located on an object research , time research, literature that used , the theory that is used and the results of the study